A expressão
é igual a:
a)
b)
c)
d) 7
Soluções para a tarefa
Respondido por
2
2³.2^x-2^x.2-³/2^x+2^x.2-³=
colocar o 2^x em evidência
2^x(2³-2-³)/2^x(1+2^-3)=
8-1/8÷1+1/8=
64-1/8÷9/8=
63/8×8/9=
63/9=7
colocar o 2^x em evidência
2^x(2³-2-³)/2^x(1+2^-3)=
8-1/8÷1+1/8=
64-1/8÷9/8=
63/8×8/9=
63/9=7
Anexos:
![](https://pt-static.z-dn.net/files/d0a/ee600db769b95a8dd660cf634dd639e2.jpg)
Perguntas interessantes
Matemática,
11 meses atrás
Português,
11 meses atrás
Matemática,
11 meses atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás